THE ANALYSIS OF EARNING PERSISTENCE (AN EMPIRICAL STUDY ON KOMPAS100 INDEX LISTED ON IDX 2018-2021) - Fillio, Venson; Diana, Patricia (Universitas Multimedia Nusantara, 2024)
Abstract - This research explains the factors that influence earnings persistence including company size, operating cash flow, ownership structure, and debt level. Earnings persistence is important for both investors and companies because it can reflect a company's ability to manage its assets effectively and generate profits in the future. This paper analyzes earnings persistence in the largest companies by market capitalization. This research uses a purposive sampling method and multiple linear regression for data analysis. This study finds that firm size has no significant influence on earning persistence, operating cash flow has a significant positive influence on earning persistence, ownership structure has a significant positive influence on earning persistence, DER has no significant negative influence on earning persistence. This study concludes that a company that has supported affiliations companies and sufficient operating cash flow tend to generate earnings persistent. Keywords: Cash Flow; Debt Level; Earnings; Ownership; Size.